Prevalence of mandibular fractures - T Saravanan (Indian Journal of Dental Research, 2020)
Aim: The aim of this study was to determine the etiology, dissemination of mandibular fractures among different age, gender, and to determine the frequency of anatomic distribution in patients who reported to our institution from February 2015 to September 2015. Materials and Methods: All patients who fulfilled the selection criteria and had mandible fracture were selected for the study. The values were subjected to Z and Chi-square tests. Results: Out of 50 patients, 44 were male patients (88%) and 6 were female patients (12%). We found a peak occurrence of fractures in young adults, with mean age of 36 years. In case of etiology of fracture, road traffic accident was the most common (72%) and parasymphysis was most frequently involved site (n = 13.26%). Conclusion: In this study, the prevalence of mandibular fracture was more prevalent in male patients, especially during the third decade of life. The most common cause was road traffic accident and the more frequently affected region was parasymphysis of the mandible.